The tell-tale start - McAlpine, Gordon (McAlpine, Gordon. Misadventures of Edgar & Allan Poe, 2013)
"Edgar and Allan, the great-great-great-great-grandnephews of the famed writer Edgar Allan Poe, discover that they are entrapped in a nefarious plot that has been going on since their birth"--